MODEL DAN STRATEGI PEMBELAJARAN TEMATIK DALAM NOVEL MADOGIWA NO TOTTOCHAN - Novi Andari; Putri Rahayuningtyas (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2021)
Thematic learning is integrated learning that uses themes to link several subjects so that they can provide meaningful experiences to students. Because literary works contain elements of education and teaching, readers, including teachers, can use literature as inspiration in developing appropriate learning models and strategies for their students. One example of literary works that can be used as inspiration by teachers, especially elementary school teachers, is a literary work in the form of a novel entitled Madogiwa no Totto-chan. This novel tells the story of a school that has shaped its students to be good and successful children in the future because it implements a natural learning system that provides direct learning experiences for its students.